A review of microstrip antenna designs for TV white space applications - Chamath Kalanaka Vithanawasam; Yi Lung Then; Hieng Tiong Su (Institute of Advanced Engineering and Science, 2020)
A review on prominent microstrip antennas fabricated for TV White Space applications is presented. This paper will delve into some of the most notable microstrip antenna designs in this frequency band that have come up in recent years. They will be analyzed to identify their strengths and weaknesses, and feedback is provided on their perceived usefulness. These antennas are designed with specific intentions, such as being placed in areas prone to harsh weather, or for long distance communications. One of the most recent antenna types to enter mainstream discussion is the microstrip patch antenna, which can easily be altered to fit various applications. Methods of connectivity such as TV White Space are enthusiastically used in various applications pertaining to connectivity and various microstrip antennas have been designed for this purpose. A conclusion was reached on the compact shorted printed monopole antenna being the most plausible choice from the antennas that have been considered and discussed.